Ontologi Matematika - Zulmaulida, Rahmy; Husna, Misratul; Saputra, Edy (Jumper: Journal of Educational Multidisciplinary Research, 2024)
This study explores mathematical ontology, an interdisciplinary field aimed at understanding the nature of the existence of mathematical concepts. Mathematics is a universal language that plays a crucial role in various disciplines. However, the complexity and abstraction of mathematical concepts often make their understanding and application challenging. This research employs a qualitative literature review method to investigate the development of thought and debates in mathematical ontology. The results of the literature analysis reveal the complexity of mathematical concepts and efforts to detail and organize mathematical ontology. This study identifies the significance of mathematical ontology in understanding mathematics, developing mathematical applications, and teaching mathematics. The research provides a deeper understanding of mathematical concepts and the fundamental structure of mathematical ontology, highlighting the potential for developing mathematical ontology in both pure and applied mathematics. The findings underscore the relevance and urgency of understanding mathematical ontology in the context of a rapidly advancing scientific and technological landscape. In conclusion, mathematical ontology serves as a crucial tool in the development of mathematics, and a deeper understanding of mathematical concepts and their ontology plays a vital role in the application of mathematics across various scientific disciplines and daily life.